Higher Education as an Institutional Factor of Inclusive Recovery: Digital Competences, Accessibility and Leadership of Public Change - Azhazha, Maryna; Peliova, Jana; Nestorenko, Tetyana; Koinash, Maryna; Brovko, Olha; Alieksieieva, Hanna (Katowice : The University of Technology in Katowice Press, 2026)
The article substantiates the role of higher education as an institutional factor of Ukraine’s inclusive recovery. It proposes an authorial logic for moving from a narrow understanding of inclusion as physical accessibility to a broader model of university training for public managers who can design barrier-free services, work with data, ensure digital accessibility, organize partnerships, and make decisions based on the needs of diverse social groups. Unlike approaches focused primarily on digital competences of future leaders in the entrepreneurial university, this article emphasizes the integration of digital, social, communicative, and ethical competences in the context of post-war recovery, veteran policy, internal displacement, accessibility of public services, and community rebuilding. The article develops the “University 4I of Inclusive Recovery” model, which includes barrier diagnostics, competence-based design, practical piloting, partnership implementation, and impact assessment. It is argued that a higher education institution can serve as an educational hub, a laboratory for social innovation, and a platform for cooperation among the state, communities, businesses, and international partners.
Keywords: Higher Education; Ukraine’s inclusive recovery